On the dynamics of the H+ + D2 (v=0,j=0) ?hD+ D+ reaction: A comparison between theory and experiment - Carmona-Novillo, Estela; González-Lezana, Tomás; Roncero, Octavio; Honvault, Pascal; Launay, Jean-Michel; Bulut, Niyazi; Wrede, Eckart (My University, 2008)
The H+ + D2 (v=0,j=0) ?HD+ D+ reaction has been theoretically investigated by means of a time independent exact quantum mechanical approach, a quantum wave packet calculation within an adiabatic centrifugal sudden approximation, a statistical quantum model, and a quasiclassical trajectory calculation. Besides reaction probabilities as a function of collision energy at different values of the total angular momentum, J, special emphasis has been made at two specific collision energies, 0.1 and 0.524 eV. The occurrence of distinctive dynamical behavior at these two energies is analyzed in some detail. An extensive comparison with previous experimental measurements on the Rydberg H atom with D2 molecules has been carried out at the higher collision energy. In particular, the present theoretical results have been employed to perform simulations of the experimental kinetic energy spectra. © 2008 American Institute of Physics.
Keywords: Angular momentum; Atoms; Computer simulation; Kinetic energy; Wave packets; Collision energy; Quasiclassical trajectory calculation; Chemical reactions